La desintegración del esnob : la fotografía en la obra de Charles Baudelaire y Lucio V. Mansilla - Mariana de Cabo (Cuadernos LIRICO)
According to Víctor Goldgel (2014), the successful snob, that is to say the dandy, questions the ego’s integrity. In this way, Charles Baudelaire and Lucio V. Mansilla, as successful snobs, make the simulation a way of living. Mansilla follows Baudelaire : his desire of adopting different egos, of pretending to be what he is not. They use writing and photographic reproduction to destroy the unity of the writer’s image.